Managerial Perspectives on Integrated Marketing Communications: Use, Practice and Development in Vietnam - Pham, N.H (2009)
This research aims at exploring managerial perspectives of Integrated Marketing Communications (IMC) in terms of use, practice and development in Vietnamese market. Up to now, in the literature, there are a good number of research studies related to IMC in well developed markets such as USA, England and Korean, whereas there are almost no researcher studies on the topic which happen in developing market. Given this reality, this research is entrusted to add value to the literature by contributing findings on the same topic within the context of a developing market, particularly Vietnam.